Personality, religious belief, and locus of control in patients with reflex sympathetic dystrophy - Montes-Iturrizaga, Iván (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
Complex regional pain syndrome is a rare autoimmune and degenerative disease; it presents disproportionate painful symptomatology, trophic changes and alternations (sensory and motor). The aim of the present quantitative study is to analyse personality characteristics, religious beliefs and locus of control in 80 patients with this condition. The results indicate that the personality profiles denote a marked impact by the presence of this disease. likewise, it was determined that the internal locus of control and religiosity explain a better coping, state of recovery and favourable expectations regarding the evolution of this disease.